Encruzilhadas da organização educacional : conceito de administração, de gestão e de gerencialismo na RBPAE - Silva, Ana Lucia Calbaiser da (Universidade Federal de São Carlos, 2012)
This study aims to explain and categorize the concepts of Educational Administration, Management and Democratic Management within the Educational system presented on the Revista Brasileira de Política e Administração da Educação (RBPAE) between 1995 and 2004. Published since 1983 by the Associação Nacional de Política e Administração da Educação (ANPAE) this journal witnessed many historical moments in our society, from which two particular periods stand out: the Administrative State Reform (in the 1990s) and the reestablishment of the democracy (in the 1980s). During these two particular moments the discussion on public management received greater attention. Our study was based on the analysis of the conceptions on Educational Administration, Management and Democratic Management defended by the authors of the articles published on the magazine. This methodology enabled us to understand and categorize these conceivings. The RBPAE was used mainly by post grad researchers acting on the educational field as a means of knowledge source on educational administration, management and democratic management. The presence of these concepts on the Magazine happened because of two reasons: the number of articles and the ideas in each concept. The education management was the most studied subject during the 1980s and mid-1990s. In the late 1990s and early 2000s this trend was reversed and then the articles on educational administration outnumbered the ladder. It was analyzed under two different concepts: administration and democratic management. The ladder was less present on the studied articles. The most analyzed concept was the democratic management, which shows the preference of the Journal for these studies. In some of them the different ideas in each concept brought about some confusion. The educational management was presented as an activity related to the coordination of actions by means of organization, development and evaluation of the process collectively and hierarchically. The democratic management was presented by its political aspect and its main characteristics: the decentralization of power, collective decision-making, communication and technical improvements. Management was presented by the limitation of state management systems and self-regulation with the emphasis on evaluation and outcomes
Keywords: Escolas - organização e administração; Revista Brasileira de Política e Administração da Educação; Associação Nacional de Política e Administração da Educação; Gestão democrática; Gerencialismo; Brazilian Education Management & Policy Journal; National Association for Policy & Education Management; Educational Administration; Management; Democratic Management; CIENCIAS HUMANAS::EDUCACAO